(untitled) (Research, Society and Development, 2025)
Introduction: Retinopathy of prematurity (ROP) is one of the leading causes of blindness in children, primarily affecting newborns with very low birth weight and gestational age. It is a condition that requires timely screening and detection to guide treatment improvement. Current therapies are invasive, expensive, and partially effective. Recently, oral propranolol has been shown to be effective in preventing or treating pre-threshold retinopathy with good results. Objectives: To report the clinical case of an extremely premature infant diagnosed with retinopathy of prematurity who received oral propranolol and showed considerable improvement in the condition. Methodology: Data were obtained from the electronic and paper medical records. The study will begin after the informed consent form (ICF) is completed by the patient’s legal guardian and approval by the Research Ethics Committee. This is an observational and descriptive study, without a control group, in the form of a clinical case report. Results/Conclusion: Its scientific relevance lies in the importance and need for new therapeutic resources, less invasive, for a condition so common in premature infants.